Transitions within the Degree Course in Education: suggestions to re-orient students at university - Diana Carmela Di Gennaro; Francesco Piro; Paola Aiello (Firenze University Press, 2020)
The paper aims to present an analysis and reflection on the types of transitions which characterize the three-year Degree Course in Education at the Department of Humanities, Philosophy and Education, University of Salerno. Starting from a brief description of the specific programmes and organisation of the Degree Course due to the recent legislation on educational professions (DDL 2443/2017 and DM 378/2018), the article investigates the university transfer process of students to this Degree Course through an analysis of students' previous careers carried out during the years 2016-2019. The heterogeneity of the profiles of the students involved in this process leads to reflect on the need to implement university guidance activities by offering personalized support in order to guarantee all students an inclusive experience and a conscious construction of their professional identity.   Il fenomeno delle transizioni nel Corso di Laurea in Scienze dell'educazione: suggestioni per il ri-orientamento degli studenti Il contributo intende presentare un'analisi ed una riflessione circa le tipologie di transizioni che interessano il Corso di Laurea triennale in Scienze dell'educazione afferente al Dipartimento di Scienze Umane, Filosofiche e della Formazione dell'Università degli Studi di Salerno. Partendo da una breve descrizione della specifica configurazione curricolare che ha assunto il percorso in ragione della recente normativa che regolamenta le professioni educative (DDL 2443/2017 e D.M. 378/2018), il lavoro indaga il fenomeno dei passaggi e dei trasferimenti degli studenti verso la L-19 attraverso una ricognizione dei riconoscimenti delle carriere pregresse effettuati tra il 2016 e il 2019. L'eterogeneità dei profili degli studenti coinvolti in tale fenomeno induce a riflettere sulla necessità di implementare gli interventi di orientamento già presenti offrendo forme di supporto personalizzato che possano garantire a tutti gli studenti un'esperienza formativa inclusiva e proiettata verso una costruzione consapevole della propria identità professionale.